Short communication: Effect of the feed presentation form on the intake pattern, productive traits and rumen pH of beef cattle fed high concentrate diets - Gimeno, Antonio; Dieste, Alberto; Al Alami, Abdelmuhsen; de Vega, Antonio; Castrillo, Carlos; Fondevila, Manuel (Spanish Journal of Agricultural Research, 2014)
Nutritional disorders like ruminal acidosis are common in Spanish beef production system, in which animals are fed diets with a high content in starch. This experiment studied the effect of feed presentation form (concentrate and straw offered separately, CD, or mixed in form of briquettes, BR) on the pattern of intake, growth and rumen pH of beef cattle fed high concentrate diets. The experiment was performed with 40 Holstein male calves, 32 of them for determining feed intake pattern and productive rates, and the remaining 8, which were previously provided with a ruminal cannula, to monitor rumen pH in two 21-day consecutive periods following a change-over design. Animals fed BR reduced feed intake rate during the first hour after feeding (18.6 vs. 24.0% of daily intake p<0.001), but this diet promoted a lower rumen pH at all sampling times compared with CD (daily average of 5.98 vs. 6.33; p<0.001) and tended to promote a lower total feed intake (7.08 vs. 9.77 kg DM/d; p<0.001) and daily weight gain (1.43 vs. 1.76 kg/d; p=0.056). Offering the concentrate and the straw mixed in form of briquettes is not useful to prevent ruminal acidosis and improve growth, probably due to both a reduced particle size of straw and avoided self-regulation of straw intake along the day.